Evidence for spin fluctuations in the deep-inelastic reaction ho165 + ho165 at 8.5 mev/amu - Mc Donald, R. J.; Pacheco, A. J.; Wojniak, G. J.; Bolotin, H. H; Moretto, L. G.; Schuck, C.; Shih, S.; Diamond, R. M.; Stephens, F. S. (North-H olland Publishing Company, 1982)
Fil: Mc Donald, R. J. Comisión Nacional de Energía Atómica; Argentina